2018
DOI: 10.1038/s41467-018-03590-5
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ enhances platinum resistance of ovarian cancer cells by reprogramming H3K79 methylation

Abstract: Chemoresistance is a major unmet clinical obstacle in ovarian cancer treatment. Epigenetics plays a pivotal role in regulating the malignant phenotype, and has the potential in developing therapeutically valuable targets that improve the dismal outcome of this disease. Here we show that a series of transcription factors, including C/EBPβ, GCM1, and GATA1, could act as potential modulators of histone methylation in tumor cells. Of note, C/EBPβ, an independent prognostic factor for patients with ovarian cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 70 publications
3
83
0
Order By: Relevance
“…59,60 In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy. 61,62 In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO. We confirmed that PGC1α binds to CEBPB and is co-localized to the promoter of CPT1A; knockdown of CEBPB sensitized NPC cells to radiation therapy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…59,60 In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy. 61,62 In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO. We confirmed that PGC1α binds to CEBPB and is co-localized to the promoter of CPT1A; knockdown of CEBPB sensitized NPC cells to radiation therapy.…”
Section: Discussionsupporting
confidence: 51%
“…CEBPB expression is associated with overall survival in breast cancer and gastric cancer patients . In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy . In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO.…”
Section: Discussionmentioning
confidence: 51%
“…every other day for three times. 28,29 Tumor volumes were estimated (volume = length • width 2 • 0.52) every 4 days until tumor volume reached 2,500-3,000 mm 3 or tumor ulceration occurred. Six weeks after tumor cell inoculation (day [D] 42), mice were killed and tumor tissues were dissected immediately after death.…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
“…Presence of two or more methylated genes in patients significantly correlated with disease recurrence (hazard ratio: 1.91; p = 0.002) and shorter overall survival and disease free survival (hazard ratio: 1.96; p = 0.006) (Lin et al, 2018). Liu et al reported the prognostic potential of C/EBPβ (a transcription factor) which augments chemoresistance of ovarian cancer cells by maintaining an open chromatin state via reprogramming H3K79 methylation of multiple drug-resistance genes upon direct interaction with DOT1L (DNA methyltransferase), thus provides a new insight for more precise therapeutics options in OC by identifying and targeting the key regulators of epigenetics (Liu et al, 2018).…”
Section: Prognosismentioning
confidence: 99%